Genomic and taxonomic studies of an antarctic psychrotolerant quorum quenching bacterium, Planococcus versutus L10.15T / See-Too Wah Seng - See-Too , Wah Seng (2020)
Quorum quenching (QQ) has been suggested as an alternative to antibiotic treatments for pathogenic infections as it does not affect the viability of the pathogen and imposes minimum selection pressure promoting drug resistance. During an ecological survey for quorum quenching (QQ) bacteria from soil collected in Lagoon Island (Ryder Bay, Adelaide Island, Antarctica), a bacterial strain was isolated and identified as Planococcus species, L10.15T, based on 16S rRNA gene analysis. The genomic, phylogenetic, chemotaxonomic and phenotypic data obtained showed that L10.15T represents a novel species for which the name Planococcus versutus sp. nov. is proposed. Previously, QQ activity of L10.15T was studied, and it was confirmed to be capable of inactivating synthetic N-acyl homoserine lactones (AHLs) with acyl side chain lengths C4-C12, and active at a temperature as low as 4 °C. In this study, the gene responsible for the QQ activity of P. versutus L10.15T was identified and confirmed for its function in a gene expression study. The cold-active characteristics of the enzyme coded by this gene suggested that it belonged to a novel class of N-acyl homoserine lactonase, and we therefore term the gene as ‘autoinducer degrading gene from Planococcus sp.’ (aidP). The aidP gene was then cloned, and its gene product AidP enzyme, which is a novel class of AHL lactonase from the metallo-ß-lactamase superfamily gene, was characterized. Multiple sequence alignment analysis and amino acid composition suggested that the aidP gene encoded a cold-adapted enzyme. Interestingly, the aidP gene has only been detected in Planococcus spp. that have been isolated from Antarctica. Therefore, branch-site analysis was conducted on several Planococcus spp. branches within the phylogenetic tree of homologous gene, showing evidence of episodic positive selection for the aidP gene in cold environments. The gene showed homology to several metallo-β-lactamase proteins obtained from Bacteroidetes but not to any known AHL-degrading enzymes. Liquid chromotography-mass spectrometry analysis confirmed that AidP functions as an AHL-lactonase that hydrolyzes the ester bond of the homoserine lactone ring of AHLs. Furthermore, the effects of covalent and ionic bonding were demonstrated and the results indicate that Zn2+ is important for AidP activity in vivo. A pectinolytic inhibition assay using Chinese cabbage confirmed that this enzyme is a potential anti-quorum sensing agent. A phylogenomic study was also carried out for members of the family Planococcaceae. The results identified a misclassification of the genus Planomicrobium, which should be reclassified to Planococcus. The core genomic study revealed an essential set of survival genes shared across Planococcaceae. A positive selection assessment conducted on the 352 core genes identified 50 genes to be under high selection pressure in cold-adapted Planococcus spp. Finally, cold-adapted traits were identified in Planococcus spp., revealing information about cold-adaptation strategies in cold habitats.